Interventions to increase seasonal influenza vaccine coverage in healthcare workers: A systematic review and meta-regression analysis. Issue 3 (3rd March 2016) - Lytras, Theodore; Kopsachilis, Frixos; Mouratidou, Elisavet; Papamichail, Dimitris; Bonovas, Stefanos
ABSTRACT: Influenza vaccination is recommended for healthcare workers (HCWs), but coverage is often low. We reviewed studies evaluating interventions to increase seasonal influenza vaccination coverage in HCWs, including a meta-regression analysis to quantify the effect of each component. Fourty-six eligible studies were identified. Domains conferring a high risk of bias were identified in most studies. Mandatory vaccination was the most effective intervention component (Risk Ratio of being unvaccinated [RRunvacc ] = 0.18, 95% CI: 0.08–0.45), followed by "soft" mandates such as declination statements (RRunvacc = 0.64, 95% CI: 0.45–0.92), increased awareness (RRunvacc = 0.83, 95% CI: 0.71–0.97) and increased access (RRunvacc = 0.88, 95% CI: 0.78–1.00). For incentives the difference was not significant, while for education no effect was observed. Heterogeneity was substantial (τ 2 = 0.083). These results indicate that effective alternatives to mandatory HCWs influenza vaccination do exist, and need to be further explored in future studies.